Classification of the extreme points of L_s(^2l_∞^3) by computation - Kim, Sung Guen (Carpathian Mathematical Publications, 2022)
Let l_∞^3=R^3 be endowed with the supremum norm. In [Comment. Math. 2017, 57 (1), 1-7], S.G. Kim classified the extreme points of the unit ball of L_s(^2l_∞^3) only using Mathematica 8, where L_s(^2l_∞^3) is the space of symmetric bilinear forms on l_∞^3. It seems to be interesting and meaningful to classify the extreme points of the unit ball of L_s(^2l_∞^3) without using Mathematica 8. The aim of this paper is to make such classification by mathematical calculations.